The Effect of Dolomite-Enriched Manure on Improving Low pH Soil in Pakcoy Cultivation - Rahmawati; Nurjanah, Eva; Fathurrahman, Ariez; Faqih, Achmad (International Journal Labs, 2025)
Acidic soil is one of the major constraints in the cultivation of horticultural crops, including pakcoy (Brassica rapa L.), as low soil pH can hinder nutrient absorption and root development. This study aimed to evaluate the effect of goat manure enriched with dolomite lime on improving soil chemical properties and enhancing the growth and yield of pakcoy grown in low-pH soil. The research was conducted in Cisantana Village, Cigugur Subdistrict, Kuningan Regency, using a randomized complete block design (RCBD) with a single factor consisting of five treatments and five replications. The treatments included: A (control), B (10 tons/ha of goat manure), C (10 tons/ha of goat manure + dolomite), D (20 tons/ha of goat manure), and E (20 tons/ha of goat manure + dolomite). Observed parameters were plant height, number of leaves, root volume, fresh plant weight, edible weight, relative growth rate, final soil pH, and organic carbon content. Data were analyzed using analysis of variance followed by the Scott–Knott test. The results showed that the application of goat manure combined with dolomite significantly improved soil pH and enhanced the growth and yield of pakcoy. Treatment E produced the best results in most measured parameters. Therefore, the integration of goat manure and dolomite lime is an effective strategy for ameliorating acidic soils and sustainably boosting pakcoy productivity.